Acute scaphoid fractures: guidelines for diagnosis and treatment. Issue 2 (3rd February 2020) - Clementson, Martin; Björkman, Anders; Thomsen, Niels O. B.
Abstract : In cases of suspected scaphoid fracture where the initial radiographs are negative, a supplementary MRI, or alternatively CT, should be carried out within three to five days. Fracture classification, assessment of dislocation as well as evaluation of fracture healing is best done on CT with reconstructions in the coronal and sagittal planes, following the longitudinal axis of the scaphoid. After adequate conservative management, union is achieved at six weeks for approximately 90% of non-displaced or minimally displaced (≤ 0.5 mm) scaphoid waist fractures. Scaphoid waist fractures with moderate displacement (0.5–1.5 mm) can be treated conservatively, but require prolonged cast immobilization for approximately eight to ten weeks. Internal fixation is recommended for all scaphoid waist fractures with dislocation ≥ 1.5 mm. Distal scaphoid fractures can be treated conservatively. The majority heal uneventfully after four to six weeks of immobilization, depending on fracture type. In general, proximal scaphoid fractures should be treated with internal fixation. Cite this article: EFORT Open Rev 2020;5:96-103. DOI: 10.1302/2058-5241.5.190025